Electrolyte disorders and aging: risk factors for delirium in patients undergoing orthopedic surgeries. Issue 1 (December 2016) - Wang, Li-Hong; Xu, Dong-Juan; Wei, Xian-Jiao; Chang, Hao-Teng; Xu, Guo-Hong
Abstract Background At present, the exact mechanism of postoperative delirium has not been elucidated. The purpose of this study was to analyze the incidence of delirium in patients undergoing orthopedic surgeries and to explore possible related factors. Methods This is a retrospective study. We used 582 patients who had undergone orthopedic surgery between January 2011 and December 2014. The surgeries consisted of 155 cases of internal fixation for intertrochanteric fracture (IFIF), 128 cases of femoral head replacement (FHR), 169 cases of total hip arthroplasty (THA) and 130 cases of total knee arthroplasty (TKA). Among the 582 patients, 75 developed postoperative delirium (an incidence of 12.9%). The demographics of the patients, which included age, gender, operation duration and blood loss, were statistically analyzed with univariate logistic regression analysis and then multivariate logistic regression. To investigate the influences of different electrolytes disorders for postoperative delirium, the Chi-square test was used. Results Multivariate logistic regression analysis indicated that postoperative delirium incidence in patients aged 70–79 years and in patients aged ≥80 years was higher than that in patients aged <70 years, odds ratio (OR) values were 6.33 and 26.37, respectively. In addition, the incidence of postoperative delirium in the group of patients with electrolyte disorders was higher than that in the normal group (OR, 2.38). There were statistically significant differences between the delirium group and the non-delirium group in the incidences of the sodium and calcium disorders. Conclusions Aging and postoperative electrolyte disorders (hyponatremia and hypocalcemia) are risk factors for postoperative delirium in patients undergoing orthopedic surgeries.